Emphasis on the Gospel and Christian Reform in Late Medieval Preaching - Petry, Ray C. (Church history, 1947)
Christian history demonstrates repeatedly that the church at its best has been a self-criticizing institution. Furthermore, the call to both corporate and individual reformation has never ceased to be regarded as the special obligation of Christian, preachers. Their hearers through the centuries have often been, highly sensitive, as individuals and groups, to castigation of any kind emanating from whatever quarter. In every era, however, there have been some prophetic spokesmen who have continued to take seriously the censures of the church's enemies and to call for self-examination, repentance, and rededication—both personal and social—on the part of its true friends.